Breaking Barriers: Enhancing the Engagement of Persons with Disabilities in Policy Making of Bangladesh - Abdur Rohim; Jakirul Islam; Bristy Khatun; Mst. Asiya Khatun; Murshida Khatun; Md Amirul Islam (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
Disability is any physical or mental condition of a person that makes it more difficult to do certain activities and interact with all over the world. Although several policies have been taken by the government and are being implemented for disabled persons where 10% of the total population of Bangladesh are facing disabilities. This study reveals how to enhance the engagement of persons with Disabilities (PWD) in policy-making in Bangladesh and also will have the capacity to achieve the 10th objective of sustainable development Goals (SDGs). The research paper utilizes qualitative and quantitative methods. Purposive sampling is employed by the researchers. The researchers intentionally selected eligible participants. The criteria comprised (1) participants with disabilities, (2) participants from various regions of Bangladesh who migrated to Rajshahi for educational purposes, and (3) participants aged between 18 and 35 years. The researchers gathered information from a total of 67 eligible participants through a survey. Drawing upon the collected data, this study aims to establish a suitable framework that guarantees the involvement of individuals with disabilities in the process of policy formation. Utilizing both Qualitative and Quantitative data, this study will formulate informed decisions concerning the circumstances of individuals with disabilities within a nation. This study offers theoretical and practical solutions for disabled individuals' challenges in policy-making in Bangladesh. The aim is to enhance the involvement of disabled people in the policy-making process.